(untitled) (Medical Forum Monthly, 2024)
Objective: To evaluate hemostatic Abnormalities in Diabetic patients via deranged PT, APTT and D-dimer. Study Design: Descriptive study Place and Duration of Study: This study was conducted at the Pathology Department, Bacha Khan Medical College and MMC Teaching Hospital Mardan from September 2016 to June 2017. Materials and Methods: In study 100 patients of Diabetes Mellitus (type-2) and 50 healthy cases as control were included. Sample was divided into Group A and Group B, each with 50 patients on the basis of glucose levels, 200-300 mg/dl and 300-400 mg/dl respectively. In all these patients Hemostatic markers were studied. Results: In Group A, 25 patients had elevated D-dimer level. Among 20 of them D-dimer level was 250-500 ng/ml and 5 had 500-1000 ng/ml level, however 3 patients had shortened PT, mean value 12.562±0.432 seconds while APPT was normal. In Group B 27 patients had raised D-dimer level. Among 20 of them D-dimer value was 500-1000 ng/ml and 7 had 250-500 ng/ml. However 2 patients had shortened PT and 2 had prolonged APTT. Mean values of 13.562±0.232 and 43.562±0.262 seconds respectively. This study show that PT and APTT were not significantly altered, while D-dimer level was significantly elevated in both groups in comparison to control group, P<0.00326 and P<0.00322 respectively. Conclusion The study concluded that Diabetes Mellitus is associated with significant hemostatic abnormalities and deranged hemostatic markers identify patients prone complications and helps in reducing morbidity and mortality in Diabetic patients.